An Advanced Receiver Autonomous Integrity Monitoring (ARAIM) Ground Monitor Design to Estimate Satellite Orbits and Clocks. (28th September 2020) - Zhai, Yawei; Patel, Jaymin; Zhan, Xingqun; Joerger, Mathieu; Pervan, Boris
Abstract : This paper describes a method to determine global navigation satellite systems (GNSS) satellite orbits and clocks for advanced receiver autonomous integrity monitoring (ARAIM). The orbit and clock estimates will be used as a reference truth to monitor signal-in-space integrity parameters of the ARAIM integrity support message (ISM). Unlike publicly available orbit and clock products, which aim to maximise estimation accuracy, a straightforward and transparent approach is employed to facilitate integrity evaluation. The proposed monitor is comprised of a worldwide network of sparsely distributed reference stations and will employ parametric satellite orbit models. Two separate analyses, covariance analysis and model fidelity evaluation, are carried out to assess the impact of measurement errors and orbit model uncertainty on the estimated orbits and clocks, respectively. The results indicate that a standard deviation of 30 cm can be achieved for the estimated orbit/clock error, which is adequate for ISM validation.